2022
DOI: 10.1021/acsaelm.2c00912
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Atomic Structures and Chemical States of Active and Inactive Dopant Sites in Mg-Doped GaN

Abstract: We employed photoelectron spectroscopy (PES) and photoelectron holography (PEH) to clarify the atomic structures and chemical states in the active and inactive dopant states of Mg-doped GaN. Due to the lack of available direct evidence, this has been a controversial issue. From PES, we found that two chemical states existed in the Mg-doped GaN: One is an active dopant state, and the other is an inactive state. We employed PEH to investigate the two observed chemical states, indicating that the active state cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Thus, the Al dopant shows a lower binding energy than metal Al. This phenomenon is observed in p-type wide-bandgap semiconductors …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus, the Al dopant shows a lower binding energy than metal Al. This phenomenon is observed in p-type wide-bandgap semiconductors …”
Section: Resultsmentioning
confidence: 71%
“…This phenomenon is observed in p-type wide-bandgap semiconductors. 54 Figure 7(a) shows the Al K-edge XANES spectrum for Aldoped 4H-SiC(0001) measured by TEY and the simulated XANES spectra. In the experiment's XANES spectrum, a pre- edge peak appears at 1556 eV, and it is attributed to the 1s→ p transitions, where p states are hybridized with Al 3s states.…”
Section: Al-doped 4h-sic(0001)mentioning
confidence: 99%
“…Surface etching was performed in the chamber by using Ar ion milling. Photoelectron holography, a type of atomic resolution holography that can directly reveal a three-dimensional local structure around a target atom [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], was performed by using soft X-ray as a light source at the beamline 25SU [ 64 ] of the synchrotron radiation facility Super Photon ring-8 GeV (SPring-8), Japan. A wide-angle display-type retarding field analyser was used for the measurement [ 65 ].…”
Section: Calculation and Experimental Methodsmentioning
confidence: 99%
“…Among metals, it's worth nothing that Mg and Cu are nutritionally essential, environment-friendly, low cost, nontoxic, and high natural abundance. In addition, Doping Mg 2+ (s 2 ) and Cu 2+ (d 9 ) into the host lattices of the traditional II-VI and III-V QDs have been successful in achieving modulation of their optical and electronic performance [20][21][22]. Samanta et al reported that Mg 2+ is the best alternative to Pb 2+ in the CsPbX 3 crystal lattice [23], and Mg doping can dramatically improve PLQY ( ∼79%) and stability of blue emitting CsPbCl3 NCs [24][25][26].…”
Section: Introductionmentioning
confidence: 99%